Behavioral and experimental economics can inform public policy: some thoughts - Arno Riedl (Center for Economic Studies and ifo Institute (CESifo), 2009)
Experimental and behavioral economics are well established branches in the economic science. This essay presents and discusses some results and behavioral regularities from these fields which are of potential importance for public policy. After a brief introduction of what experimental and behavioral economics is, some behavioural regularities as presentation and framing effects, pro-social behavior, and reciprocity are introduced and it is reported how they interact with prominent trading institutions, taxation, and social and individual well-being. Throughout some implications for public policy are discussed.
Keywords: C90; D00; H00; 330; public economics; experimental economics; behavioral economics; public policy